2018
DOI: 10.1371/journal.pone.0208500
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maximal respiratory pressures and multiple childbearing in Brazilian middle-aged and older women: A cross-sectional community-based study

Abstract: ObjectivePrevious studies show that multiparity and a number of chronic conditions are correlated among women. Also, low respiratory muscle strength has been associated to adverse health outcomes such as chronic lung disease and early mortality. This study aimed to investigate associations between the number of lifetime pregnancies and maximal inspiratory/expiratory pressures.MethodsIn a cross-sectional study, 204 women ages 41–80 years-old, from the rural community of Santa Cruz, Brazil, provided data regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Santa Cruz is located in the countryside, 122 km from Natal and has approximately 39,660 inhabitants. This article presents a secondary analysis of data from a research study that aimed to examine the influence of menopause and hormone levels on sarcopenia and physical function (Azevedo et al, 2018;Câmara et al, 2015a). Data were collected between 2014 and 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Santa Cruz is located in the countryside, 122 km from Natal and has approximately 39,660 inhabitants. This article presents a secondary analysis of data from a research study that aimed to examine the influence of menopause and hormone levels on sarcopenia and physical function (Azevedo et al, 2018;Câmara et al, 2015a). Data were collected between 2014 and 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, among the aforementioned studies, only one determined plethysmographic LFD [6]. Other studies evaluated the impacts of parity on respiratory muscle strength [17, 21] and physical function [18, 30] of healthy females, and some others included females with chronic diseases [ eg , COPD [20], protease inhibitor phenotype [19], diabetes [31] and sleep-apnea syndrome [29]]. This study showed that the G 2 compared to the G 1 , and C 2 or C 3 compared to C 1 , had a tendency towards lung-hyperinflation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data were collected using the ATS questionnaire [28], widely described elsewhere [8, 10, 24]. Parity, defined as the number of offspring a female has borne, was introduced in three forms: numerical (unit), two groups [G 1 (parity ≤ 6); G 2 (parity > 6)] and three classes [C 1 : 1 ≤ parity ≤ 4; C 2 : 5 ≤ parity ≤ 8; C 3 : parity ≥ 9] [17, 2931]. Menopausal status was determined using the stages of reproductive aging workshop classification [32].…”
Section: Population and Methodsmentioning
confidence: 99%
“…These hormonal alterations cause a decrease in muscle strength, decreased relaxation of bronchial smooth muscle and increased compression of the thoracic spine due to osteoporosis, directly interfering with the functioning of the pulmonary system [ 10 ]. Still related to women’s health particularities, there is also evidence that multiparity is related to limited inspiratory strength, where the higher the number of pregnancies, the lower the values of maximal inspiratory pressure [ 12 ]. All these aspects show how inspiratory muscles strength may be influenced by different female health variables and could be associated with others.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is certain evidence in the literature that increasing the efficiency of respiratory muscles improves postural balance in elderly people [ 17 20 ], few investigations have been carried out considering the relationship between postural balance and objective measurements (such as maximal respiratory pressures) of muscle strength in exclusively female populations [ 17 , 21 ] associated with functions altered by the changes occurring during the aging process, and in addition to the subject’s reproductive history [ 11 , 12 , 15 ]. So, it is of extreme importance to develop research in this specific field in order to direct the assessments and consequently, the treatments for this population, considering objective evaluation techniques.…”
Section: Introductionmentioning
confidence: 99%